Rank Chasing: Do Fractiles of Returns Affect Mutual Fund Inflow Distribution? - GHOSH, Aurobindo (Institutional Knowledge at Singapore Management University, 2007)
In this paper, we describe QUARK(QUality Assurance framewoRK) that enables assessments of the performance of a specification miner in generating temporal specification of software through traces recorded from its API interaction. QUARK requires the temporal specification produced by the miner to be expressed as an automaton. It accepts a user-defined simulator automaton and a specification miner. It produces quality assurance measures on the specification generated by the miner. Extensive experiments on 3 specification miners have been performed to demonstrate the usefulness of our proposed framework.